“Testing for Malaria does not Cure any Pain” A Qualitative Study Exploring Low Use of Malaria Rapid Diagnostic Tests at Drug Shops in Rural Uganda - Shelus, Victoria; Mumbere, Nobert; Masereka, Amos; Masika, Bonita; Kiitha, Joackim; Nyangoma, Grace; Mulogo, Edgar M.; Barrington, Clare; Baguma, Emmanuel; Muhindo, Rabbison; Boyce, Ross M. (PLOS Global Public Health, 2022)
The World Health Organization recommends all suspected malaria cases be confirmed with a parasitological test, typically a rapid diagnostic test (RDT), prior to treatment. Despite recommendations, many fevers presenting at private drug shops are treated presumptively as malaria without diagnostic testing. The purpose of this qualitative study was to describe community perceptions of RDTs and explore ways to improve malaria case management at drug shops in Bugoye, western Uganda. A total of 63 in-depth interviews were conducted between September and December 2021 with 24 drug shop clients, 19 drug shop vendors, 12 community health workers, and 8 health and community officials. Data was analyzed using thematic content analysis and narrative techniques. While drug shop clients valued RDTs, the cost of the test limited their use. Further, mistrust in negative results and fear about treatment options for conditions other than malaria led to nonadherence to negative RDTs. Improvement with antimalarials after a negative RDT, or no RDT at all, was seen as proof an individual had malaria, reinforcing the acceptability of liberal antimalarial use. Drug shop vendors were knowledgeable about malaria case management but financially conflicted between recommending best practices and losing business. While clients viewed drug shop vendors as trusted health professionals, health officials distrusted them as business owners focused on maximizing profits. Study results suggest public-private partnerships that recognize the essential role of drug shops, better incorporate them into the healthcare system, and leverage the high levels of community trust in vendors, could provide greater opportunities for oversight and training to improve private-sector malaria case management. Interventions that address financial barriers to RDT use, emphasize the financial benefits of malaria testing, increase vendor knowledge about illnesses confused with malaria, and improve the quality of vendor-client counseling could increase RDT uptake and improve adherence to RDT results.
Keywords: Drug shops; Testing; Malaria; Rapid diagnostic tests